Pengaruh Stimulasi Pijat Bayi terhadap Pertumbuhan Berat Badan Bayi Usia 4-6 Bulan - Ade Nurhasanah Amir; Febby Herayono; Silvie Permatasari; Ika Yulia Darma (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The development of babies 0-6 months is the most important and critical period in addition to needing good nutrition, babies also really need stimulation to achieve optimal growth and development. Stimulation can be done on the baby is baby massage to help the baby's development. The purpose of the study was to determine the effect of massage on infant weight growth. This type of research uses a quasi-experimental pre and post test design. The sample in this study amounted to 16 infants divided into the intervention and control groups. The side technique in this study was accidental sampling by intervening in the treatment group for 30 days. The results for the univariate analysis showed that the average weight of the babies before the intervention was 8.6 kg after the intervention for 30 days, the baby's weight was measured and the post test results were 9.2 kg for the treatment group while for the control group The pretest obtained 7.5 kg and then weighed again after 30 days without intervention, the baby's body weight was 7.7 kg. The results of the bivariate analysis obtained a p value of 0.028 which means that there is an effect of giving baby massage to the addition of the baby's body weight.